2015
DOI: 10.1093/scan/nsv102
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral glucose metabolism differentiates danger- and non-danger-based traumas in post-traumatic stress disorder

Abstract: Post-traumatic stress disorder (PTSD) is presumably the result of life threats and conditioned fear. However, the neurobiology of fear fails to explain the impact of traumas that do not entail threats. Neuronal function, assessed as glucose metabolism with (18)fluoro-deoxyglucose positron emission tomography, was contrasted in active duty, treatment-seeking US Army Soldiers with PTSD endorsing either danger- (n = 19) or non-danger-based (n = 26) traumas, and was compared with soldiers without PTSD (Combat Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Neuro-imaging studies have indicated that dangerbased and non-danger-based stressors activate quite different locations in the brain. Ramage et al (2015) found that only danger-based stressors elicited increased metabolic activity in the fear circuitry involving the amygdalae. In contrast, the non-danger-based stressors increased the metabolism in the precuneus, a part of the medial parietal cortex involved in episodic memory and self-processing operations (Cavanna & Trimble, 2006).…”
Section: 派遣至阿富汗的挪威退伍军人中危险和非危险应激源及其与创伤后损伤 或成长的关系mentioning
confidence: 98%
See 3 more Smart Citations
“…Neuro-imaging studies have indicated that dangerbased and non-danger-based stressors activate quite different locations in the brain. Ramage et al (2015) found that only danger-based stressors elicited increased metabolic activity in the fear circuitry involving the amygdalae. In contrast, the non-danger-based stressors increased the metabolism in the precuneus, a part of the medial parietal cortex involved in episodic memory and self-processing operations (Cavanna & Trimble, 2006).…”
Section: 派遣至阿富汗的挪威退伍军人中危险和非危险应激源及其与创伤后损伤 或成长的关系mentioning
confidence: 98%
“…Furthermore, several studies suggest that various types of traumatic stressors may produce different symptomatic outcomes. Generally, danger-based stressors are associated with a hyperarousal symptom cluster, while non-danger-based stressors seem associated rather with a depression symptom cluster (Pietrzak et al, 2011;Ramage et al, 2015;Shea et al, 2017;Stein et al, 2012). Moreover, non-danger-based stressors may precipitate more posttraumatic distress than the dangerbased stressors (Litz et al, 2009;Nash et al, 2010;Ramage et al, 2015).…”
Section: 派遣至阿富汗的挪威退伍军人中危险和非危险应激源及其与创伤后损伤 或成长的关系mentioning
confidence: 99%
See 2 more Smart Citations
“…In an 18 F-FDG PET study on active-duty treatment-seeking U.S. army soldiers with PTSD who experienced danger-based trauma, decreased metabolism in the left amygdala was associated with PTSD severity. In PTSD patients without danger-based trauma, decreased metabolism in the right amygdala was associated with PTSD severity (46). Recent studies have also explored discrete amygdala subregions involved in encoding of emotional events, including the basolateral subdivision and the centromedial amygdala ( The medial prefrontal cortex has been consistently established as a region involved in emotional regulation, and its failure to inhibit the amygdala in PTSD has been thought to lead to impaired fear extinction.…”
Section: Amygdalamentioning
confidence: 99%